Typification of the two Arariba names published by Martius and of the two Pinckneya names published by Allemão & Saldanha, synonymous with the names of two species of Simira (Rubiaceae, Condamineeae) - Margalho, Luciano Ferreira; Delprete, Piero G.; Groppo, Milton (Phytotaxa, 2020)
Martius described the genus Arariba, with two species, A. rubra and A. alba from material collected in the Brazilian state of Rio de Janeiro, which are here lectotypified. Twelve years later, Allemão and Saldanha described Pinckneya rubescens and P. viridiflora, also from material collected in Rio de Janeiro; the holotypes of these two Pinckneya names have recently been found in the Herbarium of the National Museum of Rio de Janeiro. After comparative studies of their types and recent collections, we concluded that these taxa are synonymous with Simira alba (Mart.) comb. nov. and Simira rubra. Comments on typification and critical historical collections of all taxa involved are also provided.